Decatungstate Photocatalyzed Benzylation of Alkenes with Alkylaromatics. Issue 14 (9th October 2013) - Qrareya, Hisham; Ravelli, Davide; Fagnoni, Maurizio; Albini, Angelo
Abstract The direct benzylation of electrophilic alkenes with alkylbenzenes has been achieved by decatungstate photocatalysis in a high ionic strength medium (5:1 acetonitrile/water mixed solvents, 0.5 M lithium perchlorate). The reaction has been extended to ring‐substituted (Cl, F, CN) toluenes and further alkylbenzenes. Intramolecular selectivity (p‐cymene, 4‐methylanisole) and deuteration effects support the atom transfer character of the process that, however, requires a sufficient stabilization of the intermediate polar exciplex to occur. The reactivity of the decatungstate anion is compared with that of aromatic ketones, the benchmark of photochemical hydrogen/electron transfer processes. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>